EFL Students’ Problems in Writing Argumentative Essays - Busthomi; Ahmad Munir; Lies Amin Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing in a foreign language is not easy because students have to consider not only the content but also the vocabulary, grammar, and mechanics. This study aimed to investigate the problems that English students have in writing argumentative essays. The subjects of this research were 55 students who were enrolled in Advanced Writing course at English Language Education Study Program of FKIP Universitas Lambung Mangkurat. A descriptive design within mixed method approaches was applied. A questionnaire was distributed and an open-ended interview was carried out to reveal problems that students face in writing argumentative essays. Moreover, an analysis on students’ argumentative essays was employed to confirm the findings from the questionnaire and interview. The results indicated that the students had problems in writing argumentative essays pertaining to cognitive aspects (lack of knowledge on the key features of an argumentative essay), linguistic aspects (content, grammar, organization, vocabulary, claim, and evidence), and psychology aspects (fear of making mistakes, lack of self-esteem, and low motivation) that affected them in writing. These findings demand attention from the lecturers of Advanced Writing course particularly on the needs of more explicit instruction on writing claims and providing evidence in argumentative essays. The findings also suggest that more effective approach of teaching argumentative writing is needed to overcome students’ problems.